(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The aim of the current research is to identify the need for social support among a sample of Damascus University students and its relationship to the intensity of exposure to social communication sites to obtain satisfaction of this need. The research was conducted on a sample that included (260) male and female students in some of the applied and theoretical colleges. The sample was chosen randomly, The measure of the needs was used by the researcher, and an information form was also used to measure the intensity of exposure to social communication sites /the researcher’s preparation/ and the classification search variables included the study type (Applied / Theory) and the year of the study (first / last) and gender (male / female). The research concluded the following results: • There was a statistically significant relationship between the need for social support among university students (the research sample) and the intensity of their exposure to social communication • There were statistically significant differences between university students in the need for social support and the intensity of their exposure (low, medium, and high) to social communication sites in favour of the most exposed students. • There were no statistically significant differences between university students (male and female) in the need for social support and the intensity of their exposure to social communication sites. • There were statistically significant differences between students of theoretical colleges and applied colleges in the need for social support and the intensity of their exposure to social communication sites in favor of theoretical colleges. • There were statistically significant differences between first year students and last year students in the need for social support and the intensity of their exposure to social communication in favor of students of the last year. In light of the results the research offered the following suggestions: • Reconsideration of the investment of social communication sites by the university administration and attention to the contents of these sites due to the high intensity of exposure of university students to them. • Working to open an office to provide social and counseling service in various colleges. • Knowing the needs and motives of students and ways to satisfy them, especially in recent school years, which is reflected in the safety of their adaptation and the satisfaction of their different needs.